2014
DOI: 10.1021/jm500312x
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Structure–Activity Relationship Studies of Novel Thioether Pleuromutilin Derivatives as Potent Antibacterial Agents

Abstract: A series of novel thioether pleuromutilin derivatives incorporating various heteroaromatic substituents into the C14 side chain have been reported. Structure-activity relationship (SAR) studies resulted in compounds 52 and 55 with the most potent in vitro antibacterial activity among the series (MIC = 0.031-0.063 μg/mL). Further optimization to overcome the poor water solubility of compound 55 resulted in compounds 87, 91, 109, and 110 possessing good in vitro antibacterial activity with increased hydrophilici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 35 publications
2
63
0
Order By: Relevance
“…2006), and has since been used as a topical treatment for impetigo skin infections, typically caused by Gram-positive bacteria like Staphylococcus aureus and Streptococcus pyogenes . Research is still ongoing to develop novel pleuromutilin derivatives that could be employed as systemic antibiotics in human medicine (Ling et al., 2014, Zhang et al., 2015). One very promising compound is lefamulin, a pleuromutilin derivative developed by Nabriva Therapeutics that is soon to be entering phase III clinical trials for the treatment of moderate to severe CAPB (community-acquired bacterial pneumonia) (Prince et al., 2013, Rubino et al., 2015, Waites et al., 2016).…”
Section: Medicinal Basidiomycetesmentioning
confidence: 99%
“…2006), and has since been used as a topical treatment for impetigo skin infections, typically caused by Gram-positive bacteria like Staphylococcus aureus and Streptococcus pyogenes . Research is still ongoing to develop novel pleuromutilin derivatives that could be employed as systemic antibiotics in human medicine (Ling et al., 2014, Zhang et al., 2015). One very promising compound is lefamulin, a pleuromutilin derivative developed by Nabriva Therapeutics that is soon to be entering phase III clinical trials for the treatment of moderate to severe CAPB (community-acquired bacterial pneumonia) (Prince et al., 2013, Rubino et al., 2015, Waites et al., 2016).…”
Section: Medicinal Basidiomycetesmentioning
confidence: 99%
“…Most recently, another pleuromutilin derivative called lefamulin has been developed by Nabriva Therapeutics, and is in Phase 3 clinical trials for the treatment of moderate to severe CAPB (community-acquired bacterial pneumonia), and if approved, could become the first pleuromutilin antibiotic for systemic oral administration in humans. Pleuromutilins show no cross-resistance with other antibiotics, such as the macrolides (Waites et al, 2016), and this lack of cross resistance means pleuromutilin derivatives are also the focus of research into novel treatments for multi-drug resistant (MDR-) and extensively drug resistant (XDR-) tuberculosis (Ling et al, 2014; Dong et al, 2015). If pleuromutilin derivatives are to be deployed as affordable mass market antibiotics, there is a need to increase the production capacity of the system, both by optimization of the culture conditions and by genetic strain improvements to the producing fungus.…”
Section: Introductionmentioning
confidence: 99%
“…The antibacterial studies prove that heterocyclic ring bearing polar groups at the C14 side chain of pleuromutilin derivatives may raise their antibacterial activity [17,18]. This conclusion is supported by the work of Ling et al [16]. They designed and synthesized a serial of pleuromutilin with pyridine ring bearing amino groups which exhibit excellent in vitro antibacterial activity against both sensitive and resistant Gram-positive bacterial strains.…”
Section: Introductionmentioning
confidence: 73%
“…Structure activity relationship (SAR) study showed the synthesized pleuromutilin derivatives with a heterocyclic ring at the C14 position may increase hydrogen bonding and pep stacking interactions and thereby have strong antibacterial properties [14e16]. In addition, compounds bearing primary amine substituents at pyridine ring incorporated into the C14 side chain exhibited antibacterial activity [16]. The molecular docking results revealed the substituents with hydrogen donators, for example, hydroxy and amino group, at the C14 side chain enhance the binding affinities by hydrogen bondings and thus should be introduced to produce new analogues with higher antibacterial activities [17].…”
Section: Introductionmentioning
confidence: 99%